Agile reactive navigation for a non‐holonomic mobile robot using a pixel processor array. Issue 9 (8th March 2021) - Liu, Yanan; Bose, Laurie; Greatwood, Colin; Chen, Jianing; Fan, Rui; Richardson, Thomas; Carey, Stephen J.; Dudek, Piotr; Mayol‐Cuevas, Walterio
Abstract: This paper presents an agile reactive navigation strategy for driving a non‐holonomic ground vehicle around a pre‐set course of gates in a cluttered environment using a low‐cost processor array sensor. This enables machine vision tasks to be performed directly upon the sensor's image plane, rather than using a separate general‐purpose computer. The authors demonstrate a small ground vehicle running through or avoiding multiple gates at high speed using minimal computational resources. To achieve this, target tracking algorithms are developed for the Pixel Processing Array and captured images are then processed directly on the vision sensor acquiring target information for controlling the ground vehicle. The algorithm can run at up to 2000 fps outdoors and 200 fps at indoor illumination levels. Conducting image processing at the sensor level avoids the bottleneck of image transfer encountered in conventional sensors. The real‐time performance of on‐board image processing and robustness is validated through experiments. Experimental results demonstrate the algorithm's ability to enable a ground vehicle to navigate at an average speed of 2.20 m/s for passing through multiple gates and 3.88 m/s for a 'slalom' task in an environment featuring significant visual clutter.